(untitled) (Revista Inclusiones, 2019)
The article deals with the descriptions of novelties in Russian speech etiquette. The authors analyze greeting and farewell formulas that are currently undergoing the most significant changes. Texts from modern mass media and online communication were used as materials for the study. At present, journalists are striving to get as close to the addressee as possible and are looking for new techniques for influencing people. One such technique is using new greeting and farewell formulas. The examination of this material has revealed that due to increased competition in radio and television, addressers try to become memorable, stand out. As a result, they use new original formulas of speech etiquette. The novelty of the research is related to the relevance of the chosen topic and comes from the fact that, unlike in other studies, the authors examine greeting and farewell formulas that have become part of the Russian language during the past two years, which makes it possible to analyze the current situation. Greeting and farewell formulas are the most frequent in verbal communication, therefore, they are the most susceptible to modification.